2008
DOI: 10.1002/gps.2157
|View full text |Cite
|
Sign up to set email alerts
|

Use of medications with anticholinergic properties and cognitive function in a young‐old community sample

Abstract: This study suggests that exposure to anticholinergic medication is associated with lower level of complex attention in the young-old, but not with greater cognitive decline over time. Although the clinical significance of this is not clear, caution should be taken when prescribing medications with anticholinergic effects to older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 34 publications
2
35
1
Order By: Relevance
“…As in our study, some other studies also compared different anticholinergic exposure measures . Low et al .…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…As in our study, some other studies also compared different anticholinergic exposure measures . Low et al .…”
Section: Discussionmentioning
confidence: 58%
“…Other studies analysed global cognition using the MMSE or Saint Louis University Mental Status (SLUMS) examination , but results were inconsistent: one study found a significant association between baseline anticholinergic exposure and cognition measured with MMSE progression, whereas two studies with longer follow‐ups found no association . One study evaluated baseline anticholinergic burden and MMSE progression at 2 years in community‐dwelling adults aged 65 years or older in the UK .…”
Section: Discussionmentioning
confidence: 99%
“…The administration of anticholinergic agents to cognitively intact individuals can lead to similar changes in cognition to those seen in patients with dementia [51]. Likewise, epidemiological data link exposure to anticholinergic agents to cognitive impairment and an increase in incident diagnosis of dementia over the longer term [29,30,[52][53][54][55].…”
Section: Pharmacotherapeutic Considerations For Management Of Uimentioning
confidence: 99%
“…Certain drugs, such as atropine or oxybutynin, are used specifically because of their anticholinergic properties, while other drugs, such as antidepressants, antipsychotics and antihistamines, have anticholinergic activities that are not necessarily related to their therapeutic effects. Despite the fact that anticholinergic drugs are associated with serious adverse events, they are commonly used among older people …”
Section: Introductionmentioning
confidence: 99%